The Process of Making Fiber from Soybean Inside - Sakti, Arya Mahendra (Proceeding Series of International Conference on Arts and Humanities, 2022)
Utilization of natural fiber from soybean husk waste in the processing of dairy, tempeh, and tofu is very suitable to be development. Soybean husk waste has not had too high economic value, it can be used for making soybean husk fiber. Fulfillment of basic ingredients to produce environmentally friendly materials, a basic material made from natural vegetable fibers was developed. This fiber has two categories, namely one with protein origin and the other with cellulose origin. Fiber derived from protein comes from vegetable proteins such as corn, soybeans, beans, etc. Soybased processed products are a good source of vegetable protein, and dietary fiber, have high oligosaccharide content, contain vitamins and minerals and can reduce the risk of coronary heart disease, and carcinogenesis type diabetes, reduce negative symptoms due to menopause and improve bone health. The soybean seed husk contains a lot of crude protein 17.98%, crude fat 5.5%, crude fiber 24.84%, and metabolic energy 2898 kcal/kg. We clean the soybean husk by soaking it using guides for 2 hours, 3 hours, and 4 hours, then dried it. After that, we puree the dimensions, we give alkali treatment by soaking in NaOH solution, then drying at room temperature. For fiber from soybean husk that has been dried, we add cellulose to increase the strength of the fiber. The more mixture of soybean husk composition, the lower the mechanical properties of the fiber. The more mixture of cellulose composition, the mechanical properties of the fiber will be harder and more ductile. The longer the heating process in the manufacture of fiber dough, the more ductile the mechanical properties of the fiber will be. either.